2022
DOI: 10.1200/jco.21.01332
|View full text |Cite
|
Sign up to set email alerts
|

Panitumumab Plus Fluorouracil and Folinic Acid Versus Fluorouracil and Folinic Acid Alone as Maintenance Therapy in RAS Wild-Type Metastatic Colorectal Cancer: The Randomized PANAMA Trial (AIO KRK 0212)

Abstract: PURPOSE The randomized PANAMA trial investigated the efficacy of panitumumab (Pmab) when added to maintenance therapy with fluorouracil and folinic acid (FU/FA) in patients with RAS wild-type metastatic colorectal cancer. METHODS Following first-line induction therapy with six cycles of FU/FA and oxaliplatin plus Pmab, responding patients (stable disease or partial or complete remission) were randomly assigned (1:1, open-label) to maintenance treatment with either FU/FA plus Pmab or FU/FA alone. The primary ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 38 publications
5
53
0
Order By: Relevance
“…The median number of induction cycles was also balanced between the cohorts. These results are consistent with previously summarized literature data, as the maintenance (10)(11)(12) or intermittent (13,14) strategies have been mainly investigated in patients treated with an oxaliplatin-based chemotherapy backbone following a 6-to 12-cycle (i.e., about 3-6 months) induction in order to reduce the incidence of peripheral neuropathy. The higher proportion of patients treated with a FOLFIRI chemotherapy backbone up to disease progression, unacceptable toxicity, or patient decision in the non-maintenance compared to the maintenance cohorts, together with the higher incidence of non-hematological and hematological AEs, including diarrhea and neutropenia, emphasized the issue of dealing with irinotecanrelated cumulative toxicities and the need for comparative trials of post-induction management in this setting.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The median number of induction cycles was also balanced between the cohorts. These results are consistent with previously summarized literature data, as the maintenance (10)(11)(12) or intermittent (13,14) strategies have been mainly investigated in patients treated with an oxaliplatin-based chemotherapy backbone following a 6-to 12-cycle (i.e., about 3-6 months) induction in order to reduce the incidence of peripheral neuropathy. The higher proportion of patients treated with a FOLFIRI chemotherapy backbone up to disease progression, unacceptable toxicity, or patient decision in the non-maintenance compared to the maintenance cohorts, together with the higher incidence of non-hematological and hematological AEs, including diarrhea and neutropenia, emphasized the issue of dealing with irinotecanrelated cumulative toxicities and the need for comparative trials of post-induction management in this setting.…”
Section: Discussionsupporting
confidence: 91%
“…This survival benefit was associated with a higher incidence of hematological and non-hematological AEs, other than paronychia/nail disorders, which usually occur after several weeks of treatment with anti-EGFR, particularly in association with fluoropyrimidines ( 23 ). These results are consistent with the existing literature, corroborating the hypothesis that patients gain more in terms of PFS and OS from a maintenance approach than from a “stop-and-go” strategy ( 13 ), with an even greater benefit for FU/LV+anti-EGFR compared to anti-EGFR alone, particularly in patients affected by left-sided RAS / BRAF wild-type mCRC, at the price of a slightly higher incidence of manageable toxic effects ( 9 , 10 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast to the abovementioned anti-EGFR mAb maintenance study, the control group design of the PANAMA-AIO KRK0212 study ( Modest et al, 2022 ) orally reported at the 2021 ASCO annual meeting is more suitable for the clinical problem which hopes to solve, that is, whether there is an advantage to adding anti-EGFR mAb to maintenance therapy over fluoropyrimidine-based monotherapy maintenance modalities. This study is a multicenter, randomized, open phase III clinical study, which explored the difference in efficacy between 5-FU combined with panitumumab and 5-FU monotherapy maintenance after six cycles of first-line panitumumab plus oxaliplatin plus 5-FU in RAS wild-type patients.…”
Section: 1 Maintenance Therapy With a Single Anti-egfr Mabmentioning
confidence: 99%